E-marketing - Strauss, Judy.; Frost, Raymond (Upper Saddle River, N.J. : Pearson Prentice Hall, 2009)
"This edition focuses more on e-marketing strategy and features seven new chapter-opening vignettes, many new screen images, and updated "Let's Get Technical" boxes. Significant new topics covered include Web analytics, engagement metrics, virtual worlds, location marketing online, and an entire new chapter and appendix on the social media (including search marketing). The authors also propose a new way of looking at physical and digital media and suggest that the terms offline/online and traditional/non-traditional media no longer work." "The book retains the strong global and legal coverage and cutting-edge material that has made it a market leader since the first edition, in 1997. This long-term perspective on e-marketing strategies gives this book a competitive advantage not realized in other books in this field."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Internet marketing